logo

Ask Questions, Get Answers

X
 
Home  >>  JEEMAIN and NEET  >>  Mathematics  >>  Class11  >>  Sequence and Series

If $f\;(xy)=f\;(x+y)\;\forall\;x,y\;\in\;R$ and $\;f\;(2009)=2009$, then $f\;(-2009)$ equals

$(a)\;-2009\qquad(b)\;2009\qquad(c)\;0\qquad(d)\;None$

Download clay6 mobile app

1 Answer

Answer : (b) 2009
Explanation : $f\;(2009)=f\;(2009+0)=f\;(2009*0)$
$=f\;(0)=2009$
$f\;(-2009)=f\;(-2009+0)=f(-2009*0)=f(0)=2009.$
answered Jan 20, 2014 by yamini.v
 

Related questions

...
X